Valveless On-Chip Aliquoting for Molecular Diagnosis - Romero Deza, Andersson A. (2023)
The detection of nucleic acids as specific markers of infectious diseases is commonly implemented in molecular biology laboratories. The translation of these benchtop assays to a lab-on-a-chip format demands huge efforts of integration and automation. The present work is motivated by a strong requirement often posed by molecular assays that combine isothermal amplification and CRISPR/Cas-based detection: after amplification, a 2–8 microliter aliquot of the reaction products must be taken for the subsequent reaction. In order to fulfill this technical problem, we have designed and prototyped a microfluidic device that is able to meter and aliquot in the required range during the stepped assay. The operation is achieved by integrating a porous material that retains the desired amount of liquid after removing the excess reaction products, an innovative solution that avoids valving and external actuation. The prototypes were calibrated and experimentally tested to demonstrate the overall performance (general fluidics, metering, aliquoting, mixing and reaction). The proposed aliquoting method is fully compatible with additional functions, such as sample concentration or reagent storage, and could be further employed in alternative applications beyond molecular diagnosis.